Automated Monitoring of River Ice Processes from Shore-based Imagery - Ansari, Saber (Université d'Ottawa / University of Ottawa, 2016)
Ice plays an important role in hydraulic processes of rivers in cold regions such as Canada. The formation, progression, recession and breakup of river ice cover known as river ice processes affect river hydraulics, sediment transport characteristics as well as river morphology. Ice jamming and break up are responsible of winter flash floods, river bed modification and bank scour. River ice cover monitoring using terrestrial images from cameras installed on the shores can help monitor and understand river ice processes. In this study, the benefits of terrestrial monitoring of river ice using a camera installed on the shore are evaluated. A time-lapse camera system was installed during three consecutive winters at two locations on the shores of the Lower Nelson River, in Northern Manitoba and programmed to take an image of the river ice cover approximatively every hour. An image analysis algorithm was then developed to automatically extract quantitative characteristics of the river ice cover from the captured images. The developed algorithm consists of four main steps: preprocessing, image registration, georectification and river ice detection. The contributions of this thesis include the development of a novel approach for performing georectification while accounting for a fluctuating water surface elevation, and the use of categorization approach and a locally adaptive image thresholding technique for target detection. The developed algorithm was able to detect and quantify important river ice cover characteristics such as the area covered by ice, border ice progression and ablation rate, and river ice break up processes with an acceptable accuracy.
Keywords: river ice; terrestrial photogrammetry; shore-based